Management of Urinary Incontinence before and after Total Pelvic Reconstruction for Advanced Pelvic Organ Prolapse with and without Incontinence - Yu Song; Xiao-Juan Wang; Yi-Song Chen; Ke-Qin Hua (Chinese Medical Journal, 2018)
Background: The effectiveness of an anti-incontinence procedure concomitant with prolapse reconstruction for pelvic organ prolapse (POP) in preventing urinary incontinence (UI) after surgery remains controversial. Our study aimed to describe the incidence of pre- and postoperative UI for pelvic reconstructive surgery and evaluate the management of POP associated with UI. Methods: A total of 329 patients who underwent total pelvic reconstruction between June 2009 and February 2015 at a single institution were identified. These patients were divided into two groups (Group A [Prolift reconstruction]: n = 190 and Group B [modified total pelvic reconstruction]: n = 139). Data regarding surgical procedures and patient demographic variables were recorded. Chi-square and Student's t-tests were used for two independent samples. Results: A total of 115 patients presented with UI preoperatively. The average follow-up time was 46.5 months, with 20 patients lost to follow-up (6.1%). The cure rates of stress UI (SUI), urgency UI (UUI), and mixed UI (MUI) were 51% (30/59), 80% (16/20), and 48% (14/29), respectively. The cure rate of UUI after total pelvic reconstruction (80% [16/20]) was higher than that of SUI (50.8% [30/59], χ2 = 5.219, P = 0.03), and the cure rate of MUI (48%, 14/29) was the lowest. The cure rate of patients with UI symptoms postoperatively was lower than that of those with symptoms preoperatively (9.1% [28/309] vs. 16.2% [50/309], χ2 = 7.101, P = 0.01). There was no difference in the incidence of UI postoperatively between Groups A and B (P > 0.05). The cure rate of SUI in patients undergoing tension-free vaginal tape-obturator was not higher than that in those who did not undergo the procedure (42.9% [6/14] vs. 53.3% [24/45], χ2 = 0.469, P = 0.49). There were no differences in the cure rate for POP or UI between these two types of reconstructions (P > 0.05). Conclusions: No correlation between the incidence of UI and POP was identified. The results suggest that UI treatment should be performed after POP surgery for patients with both conditions.